Adrenal Steroids Modulate Fibroblast-Like Synoviocytes Response During B. abortus Infection - Gentilini, Maria Virginia (2019)
Brucella abortus stimulates an inflammatory immune response that stimulates theendocrine system, inducing the secretion of dehydroepiandrosterone (DHEA) andcortisol. In humans, the active disease is generally present as osteoarticular brucellosis.In previous studies we showed that B. abortus infection of synoviocytes creates aproinflammatory microenvironment. We proposed to determine the role of cortisoland DHEA on synoviocytes and infiltrating monocytes during B. abortus infection.Cortisol inhibited IL-6, IL-8, MCP-1, and MMP-2 secretion induced by B. abortusinfection in synovial fibroblast. Cortisol-mediated MMP-2 inhibition during B. abortusinfection was reversed by IL-6. DHEA inhibited B. abortus-induced RANKL up-regulationin synovial fibroblast through estrogen receptor (ER). B. abortus infection did notmodulate glucocorticoid receptor (GR) expression. Cell responses to cortisol alsodepended on its intracellular bioavailability, according to the activity of the isoenzymes11b-hydroxysteroid dehydrogenase (HSD) type-1 and 11b-HSD2 (which are involvedin cortisone-cortisol interconversion). B. abortus infection did not modify 11b-HSD1expression and GRa/b ratio in the presence or absence of adrenal steroids. Supernatantsfrom B. abortus-infected monocytes induced 11b-HSD1 in synovial cells. Administrationof cortisone was capable of inhibiting the secretion of RANKL by synoviocytes mimickingcortisol?s effect. These results go along with previous observations that highlighted theability of synovial tissue to secrete active steroids, making it an intracrine tissue. This isthe first study that contributes to the knowledge of the consequence of adrenal steroidson synoviocytes in the context of a bacterial infection.